Estrous expression of sows after altered suckling and boar exposure - Newton, E.A.; Stevenson, Jeffrey S.; Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In two different experiments, we studied the influence of: 1) separating litters from their dams (altered suckling) during the last 8 days of lactation, which included a change in housing and social interaction with other sows; 2) providing boar exposure (1 hr/d); and 3) parity on the ability of sows to come into heat during lactation and after weaning. Our studies indicated that: 1) 6 hr of altered suckling and 1 hr of boar exposure may shorten the interval to heat for sows that express estrus during lactation, but 3 hr of altered suckling and 1 h of boar exposure are sufficient to induce estrus in 65 to 79% of the sows; 2) boar exposure (1 hr /day) of sows is not sufficient to induce estrus during lactation; 3) pre weaning boar exposure (1 hr/day) reduced intervals to heat after weaning; and 4) breed composition and season may alter the responsiveness of sows to treatments that induce estrus during lactation and after weaning.
Keywords: Swine; Estrous; Sows; Boar